2007
DOI: 10.1159/000107950
|View full text |Cite
|
Sign up to set email alerts
|

Primary Invasive versus Progressive Invasive Transitional Cell Bladder Cancer: Multicentric Study of Overall Survival Rate

Abstract: Introduction and Objective: When feasible, the treatment for all-invasive bladder cancer is radical cystectomy. The aim of the present study was to analyze the prognostic difference, disease-specific survival rate, of muscle-invasive transitional cell cancer of the bladder (TCCB) for progressive invasive TCCB. Patients and Methods: A retrospective multicentric analysis was performed studying a total of 242 patients who underwent radical cystectomy for invasive TCCB from 1993 to 2005. The patients were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Both Ferreira et al [6] and May et al [7] showed similar outcomes of patients with progressive NMIBC and primary MIBC. The 5-year OSs rates were 57.9 and 51.4% for patients with progressive NMIBC and 52.2 and 47.1% for primary MIBC respectively.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Both Ferreira et al [6] and May et al [7] showed similar outcomes of patients with progressive NMIBC and primary MIBC. The 5-year OSs rates were 57.9 and 51.4% for patients with progressive NMIBC and 52.2 and 47.1% for primary MIBC respectively.…”
Section: Discussionmentioning
confidence: 80%
“…However, the oncological outcome of de novo vs. progressive MIBC patients after RC remains inconsistent in the literature, with varying and sometimes even with contradictory results regarding survival. Several authors have reported either similar or insignificantly different and comparable survival rates between the 2 groups [4,5,6,7,8,9,10,11]. Others have reported better survival in patients who progressed after initial presentation as NMIBC [12,13,14,] while yet others have reported worse prognosis if RC is performed in patients who progress to MIBC after having NMBIC [15,16.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors reported on similar prognosis [13,14] and even better prognosis for secondary T2 [15]. All these studies are limited by a small number of patients and by the inclusion of patients who underwent radical cystectomy only.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the expense of medication is a burden not only for patients themselves, but also for the economy and society (Montgomery et al, 2013). Despite the improvements made in surgical and chemotherapeutic modalities to combating bladder cancer, the 5-year survival rate still remains relative low due to highly invasiveness and metastasis of bladder cancer (Ferreira et al, 2007;Ge et al, 2012). Therefore, studies on novel medications and therapeutic modalities are warranted.…”
Section: Introductionmentioning
confidence: 99%